Synthesis, Characterization and Antimicrobial Activity of Complexes Metal Ions Ni(II), Zn(ΙΙ), Pd(II) and Pt(IV) with Polydentate 1,2,4-Triazole Ligand - Sarab Mahdi Al-Alzawi; Mahmoud Najim Al-Jibouri; Anaam Majeed Rasheed; Sinan Midhat Al-Bayati (Indonesian Journal of Chemistry, 2023)
A new ligand of 1,2,4-triazole derivative was produced by cyclization of sodium dithiocarbamate derivative of ethyl 4-ethoxy-3-nitrobenzoate with carbon disulfide in an alkaline medium. The new ligand, entitled name: L: 4-amino-5-(3-ethoxy-5-nitrophenyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione, was fully characterized depending on HPLC-MS, FTIR, 1H-NMR and 13C-NMR spectroscopies. In addition, the elemental microanalysis was carried out to confirm the skeletal structure of the ligand L. A library of complexes with Ni(II), Zn(II), Pd(II), and Pt(IV) metal ions was prepared by coordination with the ligand. These complexes were characterized by using FTIR, UV-Ѵis, 1H-NMR, 13C-NMR, spectrophotometric techniques, elemental analysis C.H.N.S, and FAAS. The physicochemical properties of these complexes were determined at 25 °C, such as melting point, magnetic susceptibility and molar conductivity. The microbial study confirmed that the novel ligand and its complexes have the potential to be applied as antimicrobial agents.